Parenting Bagi Orang Tua Muda di Pusat Pembelajaran Keluarga Surabaya Perspektif Abdullah Nashih `Ulwan - Husniyah, Azmatul (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
In this information and technology era, families face many challenges, especially in terms of childcare. The many social issues related to the family, especially the role of parents, make government institutions take the initiative to build family resilience by providing parents with knowledge about parenting. This article intends to highlight parenting activities for young parents held by the Surabaya City Government through the Puspaga (Family Learning Center) program. This program is intended to increase the knowledge of young parents about parenting towards children and make them aware of the importance of knowledge about parenting as a provision to foster harmonious families. Data was collected using interview techniques with participants and Puspaga administrators and documentation techniques. To assess this practice, the author uses child education theory according to Abdulloh Nashih 'Ulwa who emphasizes education in the fields of faith, morals, physical, psychological, resourceful, and social. The parenting program for young parents held by Puspaga is compatible with the concepts of Islamic education according to Abdullah Nashih 'Ulwa. [Tujuan utama dari penelitian ini adalah untuk mengungkapkan bahwa pendidikan parenting yang didapat oleh pemuda sebelum menikah atau di awal pernikahan dapat menyadarkan orang tua akan pentingnya pengetahuan ini terhadap tiap langkah perkembangan anak. Penelitian ini menggunakan metode penelitian kualitatif dengan melakukan wawancara dan dokumentasi dengan peserta dan stake holder di PUSPAGA Surabaya. Subyek penelitiannya adalah orang tua muda yang mengikuti training parenting di Pusat pembelajaran Keluarga (PUSPAGA) Surabaya. Dalam hal ini peneliti memakai pendidikan anak menurut Dr. Abdulloh Nashih `Ulwa. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara dan dokumentasi, dan hasinya adalah bahwa pengetahuan tentang pola pengasuhan anak atau parenting di Pusat Pembelajaran Keluarga di Surabaya yang dimiliki orang tua muda sebelum atau sesudah menikah merupakan bagian dengan parenting perspektif islam menurut Dr. Abdullah Nashih `Ulwan yaitu pendidikan keimanan, moral, fisik, psikologis, akal, fisik dan sosial.]